1980
DOI: 10.1002/cne.901930211
|View full text |Cite
|
Sign up to set email alerts
|

Brain stem projections of sensory and motor components of the vagus complex in the cat: II. Laryngeal, tracheobronchial, pulmonary, cardiac, and gastrointestinal branches

Abstract: The central sensory and motor connections of various respiratory, cardiovascular, aqd gastrointestinal viscera were analyzed using the transganglionic and retrograde transport of horseradish peroxidase (HRP).In 42 adult cats, we examined the brain stem and peripheral ganglia following microinjections of HRP (10 p1) into individual visceral organs-larynx, extrathoracic trachea, intrathoracic trachea, right main bronchus, right lung (upper lobe), heart, and stomach. Comparison of individual cases led to the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
246
2
6

Year Published

1985
1985
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 807 publications
(272 citation statements)
references
References 72 publications
17
246
2
6
Order By: Relevance
“…However, given that the properties of cough receptors differ significantly from RARs (Canning et al, 2004), the extent to which this previous information on RAR relay neurons will be useful in predicting the behavior of cough receptor second order interneurons is unknown. Based on horseradish peroxidase studies of projections of tracheal afferents (Kalia and Mesulam, 1980), it is likely that cough receptor second order interneurons are located near to or intermingled with RAR relay neurons.…”
Section: What Is the Role Of Putative Second Order Relay Neurons In Tmentioning
confidence: 99%
“…However, given that the properties of cough receptors differ significantly from RARs (Canning et al, 2004), the extent to which this previous information on RAR relay neurons will be useful in predicting the behavior of cough receptor second order interneurons is unknown. Based on horseradish peroxidase studies of projections of tracheal afferents (Kalia and Mesulam, 1980), it is likely that cough receptor second order interneurons are located near to or intermingled with RAR relay neurons.…”
Section: What Is the Role Of Putative Second Order Relay Neurons In Tmentioning
confidence: 99%
“…Recent studies indicate that the iNANC system employs vasoactive intestinal peptide (VIP) (7,16,22,38,47,57), nitric oxide (NO) (4, 30, 36, 44, 51), or both (6, 14 -16, 64) to elicit ASM relaxation. However, the preganglionic origin of neurons containing these relaxing molecules has not been established.The preganglionic motor innervation of the airways arises from the nucleus ambiguus and from the most rostral part of the dorsal motor nucleus of the vagus (DMV) (21,23,27,29,34). Inputs from these preganglionic neurons are carried by the vagal fibers that are thought to synapse with airway ganglionic cells, which in turn modify and distribute central parasympathetic outflow to the effector organs of the airways and lungs (54, 59).…”
mentioning
confidence: 99%
“…The preganglionic motor innervation of the airways arises from the nucleus ambiguus and from the most rostral part of the dorsal motor nucleus of the vagus (DMV) (21,23,27,29,34). Inputs from these preganglionic neurons are carried by the vagal fibers that are thought to synapse with airway ganglionic cells, which in turn modify and distribute central parasympathetic outflow to the effector organs of the airways and lungs (54,59).…”
mentioning
confidence: 99%
“…Studies on the innervation of the NTS have suggested that functionally classified columns are arrayed rostrocaudally in this nucleus; for example, gustatory afferents occupy the rostral third portion of the column (Whitehead and Frank, 1983; Hamilton and Norgren, 1984), while visceral afferents occupy a more caudal region (Kalia and Mesulam , 1980; Panneton and Loewy, 1980;Ciriello, 1983 Altschuler et al , 1989Altschuler et al , , 1991. Based on neurological studies showing that the NTS controls the gastrointestinal tract via the dorsal motor nucleus of the vagus (DMV) (Morest, 1967;Cottle and Calaresu, 1975;Norgren, 1978;Beckstead et aL, 1980;Rogers et aL, 1980;Arends et al , 1988), and controls the pharynx, larynx, and esophagus via the nucleus ambiguus (Amb) (Morest, 1967;Cottle and Calaresu, 1975 Cunningham et al, 1991), the NTS appears to play an important role as the afferent system of all visceromotor reflexes, including the emetic response.…”
mentioning
confidence: 99%